Bridging the accountability gap in hybrid organizations: the case of Copenhagen Malmö Port. (September 2015) - Grossi, Giuseppe; Thomasson, Anna
Previous research on hybrid organizations has drawn attention to the accountability gap that is believed to emerge when the provision of public services is transferred to a hybrid organization. In this article we take our point of departure in that research and use a case study method to explore whether this gap can be bridged by existing corporate governance systems or if governance systems specially tailored to hybrid forms need to be developed. The result of the study shows that the process is equally important as the system in place. That is, it is not only the actual system but also how the system is implemented and used that affects the ability to bridge the accountability gap. Points for practitioners: This article provides insight into how the hybrid form alters the relationship between citizens, elected politicians and organizations performing public services and, consequently, how the ability to secure accountability in public services changes. The results presented in the article provide politicians and managers in the public sector with knowledge regarding how, by focusing on organizational processes, relationships between stakeholders and performance evaluation can work with improving accountability in hybrid organizations. Further, the article stresses the need for performance evaluation to encompass not only financial aspects, but also the societal values of the public services performed by the hybrid organization.